"It Feels So Alien" or the Same Old S—: Attachment to Divergent Cultural Models in Insecure Times. (4th September 2018) - Strauss, Claudia
Abstract: Instead of conceptualizing poor people as a group with a fixed culture, we need to understand diverse, shared frameworks for responding to economic adversity. Over half of all Americans of working age can expect to be in a poor or near‐poor household at some point. Differing interpretations of their low incomes under flexible capitalism are illustrated by the responses of two unemployed middle‐aged sisters from a white working‐class family in now poverty‐stricken San Bernardino County, California. Their divergent interpretations (one blamed herself and fell into depression; the other did not) show that even members of the same subgroup can draw upon different personally compelling cultural models to navigate social and individual change. This person‐centered multiple‐cultural‐models approach is needed as a corrective both to portrayals of culture as a stable group adaptation to an unchanging economic situation and to theories of persons as buffeted by economic shifts without guiding narratives.